Strategic Alliances of Entrepreneurial Firms: Value Enhancing Then Value Destroying. (31st May 2016) - Moghaddam, Kaveh; Bosse, Douglas A.; Provance, Mike
Abstract : Research summary: Based on the RBV and dynamic capabilities, this study explains the relationship between alliance formation and the private (pre‐IPO) entrepreneurial firm's market performance. Findings show that while alliance formation positively and significantly affects the market performance of venture‐backed firms in the software industry, forming a comparatively large number of alliances hurts these firms' market valuations. Managerial summary: Entrepreneurial firms are better off entering a select number of strategic alliances and focusing on enhancing the outcomes of those select alliances as well as developing a dynamic alliance management capability. Such firms benefit most from establishing a moderate number of alliances rather than depending on a small number of alliances or becoming overwhelmed with a great number of alliances. Copyright © 2016 Strategic Management Society.